Le tarif extérieur canadien et la protection de l’activité manufacturière québécoise : nouveaux résultats (1966-1977) - Corbo, Vittorio; Martens, André (L'Actualité économique, 1980)
AbstractUsing the 1966 and 1973 (74) Quebec input-output tables we try to identify the sources of variations in the effective protection rates of 169 manufacturing activities between these two periods, namely, changes in nominal tariffs, input-output structures and international export shares. Our results suggest that, between 1969 and 1974, there were a certain number of activities where entrepreneurs used relatively more of the intermediate inputs which had become cheaper (technical substitution effect). However, most of the changes in the effective protection rate values remain explained by changes in the external nominal tariff. The impact of changes in international export shares is itself negligible. Finally the study provides the effective protection rates of the 169 activities for 1977 (given the 1973-74) input-output structure.